Optimal space manoeuvres in a non-Keplerian force field - Schulz, W.; Prado, AFBA; Kuga, H. K.; de Moraes, R. V. (Elsevier B.V., 2002)
In this work the problem of a spacecraft bi-impulsive transfer between two given non coplanar elliptical orbits, with minimum fuel consumption, is solved considering a non-Keplerian force field (the perturbing forces include Earth gravity harmonics and atmospheric drag). The problem is transformed in the Two Point Boundary Value Problem. It is developed and implemented a new algorithm, that uses the analytical expressions developed here. A dynamics that considered a Keplerian force field was used to produce an initial guess to solve the Two Point Boundary Value Problem. Several simulations were performed to observe the spacecraft orbital behaviour by different kind of perturbations and constraints, on a fuel consumption optimization point of view. (C) 2002 COSPAR. Published by Elsevier B.V. Ltd. All rights reserved.